Chromosome polymorphism of heterochromatin and nucleolar regions in two populations of the fish Astyanax bockmanni (Teleostei: Characiformes) - Hashimoto, Diogo Teruo [UNESP] (2010)
Karyotype and other chromosomal markers as revealed by C-banding and silver (Ag) impregnation in two Astyanax bockmanni populations (Barra Seca Stream and Campo Novo River) were examined. The diploid chromosome number 2n = 50 and nearly identical karyotypes were documented. C-banding revealed heterochromatic blocks on the terminal regions of some chromosomes, with high frequencies of polymorphisms. The Ag-impregnation showed that the nucleolus organizer regions (NORs) varied in number, location and organization. Astyanax bockmanni revealed chromosome characteristics similar those of the species complex A. scabripinnis. Mechanisms that may be responsible for the high degree of polymorphism are discussed. © 2010 Sociedade Brasileira de Ictiologia.